NILAI-NILAI PENDIDIKAN AKHLAK PADA ANAK PENGHAFAL ALQURAN DALAM PROGRAM TELEVISI HAFIZ INDONESIA RCTI - Fachira Jarry Jalila, - (2020)
This research is motivated by the rampant phenomenon of moral degeneration as an impact of easy access to information in the technology advancement era. One of this rampant phenomenon is influenced by the spectacle which contains negative contents. Television as a technology medium that has been familiar with society can be effective facility of instilling the education moral values. One of the television program that has positive value and can gives inspiration is Hafiz Indonesia RCTI which is a children's talent show in memorizing the Alquran. Participants of Hafiz Indonesia RCTI come from various region and bring their own background story. Therefore, it contains moral education values that can be studied and used as a moral lesson. The method that is used in this research is descriptive with qualitative approach. Data collection technique are carried out by the document study and interview. Data analyzing uses content analysis method for finding the meaning of the communication, symbols, and symbolic interaction that occur in the communication. The result of this research shows that there are moral education values in Hafiz Indonesia RCTI season 8, there are moral towards Allah consist of: Ikhlas, patience, pray, repent, grateful, tauhid, husnuzhan, tawakal; Moral towards each other; Birrul walidain, ta'awun; Moral towards ourself: Ikhtiar, love of knowledge, and optimistic. Hafiz Indonesia RCTI is one of the best television program that can be made a positive spectacle option because beside showing children's memorizing Alquran skill, they show the profile of the participants and their parents that can be made an inspiration and reference in instill the moral education values. Keyword: Moral Education Values, Hafiz Indonesia RCTI